## Middle Convolution and Heun’s Equation

^{?}

Kouichi TAKEMURA

Department of Mathematical Sciences, Yokohama City University, 22-2 Seto, Kanazawa-ku, Yokohama 236-0027, Japan

E-mail: takemura@yokohama-cu.ac.jp

Received November 26, 2008, in final form March 25, 2009; Published online April 03, 2009 doi:10.3842/SIGMA.2009.040

Abstract. Heun’s equation naturally appears as special cases of Fuchsian system of differential equations of rank two with four singularities by introducing the space of ini- tial conditions of the sixth Painlev´e equation. Middle convolutions of the Fuchsian system are related with an integral transformation of Heun’s equation.

Key words: Heun’s equation; the space of initial conditions; the sixth Painlev´e equation;

middle convolution

2000 Mathematics Subject Classification: 34M35; 33E10; 34M55

### 1 Introduction

Heun’s equation is a standard form of a second-order Fuchsian differential equation with four singularities, and it is given by

d^{2}y
dz^{2} +

γ z + δ

z−1 + z−t

dy

dz + αβz−q

z(z−1)(z−t)y= 0, (1.1)

with the condition

γ+δ+=α+β+ 1.

The parameter q is called an accessory parameter. Although the local monodromy (local expo-
nent) is independent ofq, the global monodromy (e.g. the monodromy on the cycle enclosing two
singularities) depends onq. Some properties of Heun’s equation are written in the books [21,23],
but an important feature related with the theory of finite-gap potential for the caseγ, δ, , α−β ∈
Z+^{1}_{2} (see [6,24,25,26,27,28,29,31] etc.), which leads to an algorithm to calculate the global
monodromy explicitly for allq, is not written in these books.

The sixth Painlev´e equation is a non-linear ordinary differential equation written as
d^{2}λ

dt^{2} = 1
2

1 λ+ 1

λ−1+ 1 λ−t

dλ dt

2

− 1

t + 1

t−1 + 1 λ−t

dλ dt +λ(λ−1)(λ−t)

t^{2}(t−1)^{2}

(1−θ∞)^{2}
2 −θ_{0}^{2}

2
t
λ^{2} + θ_{1}^{2}

2

(t−1)

(λ−1)^{2} +(1−θ^{2}_{t})
2

t(t−1)
(λ−t)^{2}

. (1.2) A remarkable property of this differential equation is that the solutions do not have movable singularities other than poles. It is known that the sixth Painlev´e equation is obtained by monodromy preserving deformation of Fuchsian system of differential equations,

d dz

y1

y_{2}

= A0

z + A1

z−1+ At

z−t y1

y_{2}

, A_{0}, A_{1}, A_{t}∈C^{2×2}.

?This paper is a contribution to the Proceedings of the Workshop “Elliptic Integrable Systems, Isomonodromy Problems, and Hypergeometric Functions” (July 21–25, 2008, MPIM, Bonn, Germany). The full collection is available athttp://www.emis.de/journals/SIGMA/Elliptic-Integrable-Systems.html

See Section 2 for expressions of the elements of the matrices A0,A1,At. By eliminatingy2 we
have second-order differential equation for y_{1}, which have an additional apparent singularity
z =λ other than {0,1, t,∞} for generic cases, and the point λ corresponds to the variable of
the sixth Painlev´e equation. For details of monodromy preserving deformation, see [10]. In this
paper we investigate the condition that the second-order differential equation for y_{1} is written
as Heun’s equation. To get a preferable answer, we introduce the space of initial conditions
for the sixth Painlev´e equation which was discovered by Okamoto [18] to construct a suitable
defining variety for the set of solutions to the (sixth) Painlev´e equation.

For Fuchsian systems of differential equations and local systems on a punctured Riemann sphere, Dettweiler and Reiter [2, 3] gave an algebraic analogue of Katz’ middle convolution functor [12]. Filipuk [5] applied them for the Fuchsian systems with four singularities, obtained an explicit relationship with the symmetry of the sixth Painlev´e equation, and the author [30]

calculated the corresponding integral transformation for the Fuchsian systems with four singu- larities. The middle convolution is labeled by a parameterν, and we have two values which leads to non-trivial transformation on 2×2 Fuchsian system with four singularities (see Section4). In this paper we consider the middle convolution which is a different value of the parameterνfrom the one discussed in [5,30]. We will also study the relationship between middle convolution and Heun’s equation. For special cases, the integral transformation raised by the middle convolution turns out to be a transformation on Heun’s equation, and we investigate these cases. Note that the description by the space of initial conditions for the sixth Painlev´e equation is favorable. The integral transformation of Heun’s equation is applied for the study of novel solutions, which we will discuss in a separated publication. If the parameter of the middle convolution is a negative integer, then the integral transformation changes to a successive differential, and a transforma- tion defined by a differential operator on Heun’s equation was found in [29] as a generalized Darboux transformation (Crum–Darboux transformation). Hence the integral transformation on Heun’s equation can be regarded as a generalization of the generalized Darboux transformation, which is related with the conjectual duality by Khare and Sukhatme [15].

Special functions of the isomonodromy type including special solutions to the sixth Painlev´e equation have been studied actively and they are related with various objects in mathematics and physics [16, 32]. On the other hand, special functions of Fuchsian type including special solutions to Heun’s equation are also interesting objects which are related with general relativity and so on. This paper is devoted to an attempt to clarify both sides of viewpoints.

This paper is organized as follows: In Section 2, we fix notations for the Fuchsian system with four singularities. In Section 3, we define the space of initial conditions for the sixth Painlev´e equation and observe that Heun’s equation is obtained from the Fuchsian equation by restricting to certain lines in the space of initial conditions. In Section 4, we review results on the middle convolution and construct integral transformations. In Section 5, we investigating relationship among the middle convolution, integral transformations of Heun’s equation and the space of initial conditions. In Section 6, we consider the case that the parameter on the middle convolution is integer. In the appendix, we describe topics which was put off in the text.

### 2 Fuchsian system of rank two with four singularities

We consider a system of ordinary differential equations, dY

dz =A(z)Y, A(z) = A_{0}

z + A_{1}

z−1 + A_{t}
z−t =

a11(z) a12(z)
a_{21}(z) a_{22}(z)

, Y =

y1

y_{2}

,(2.1) where t 6= 0,1, A0, A1, At are 2×2 matrix with constant elements. Then equation (2.1) is Fuchsian, i.e., any singularities on the Riemann sphere C∪ {∞} are regular, and it may

have regular singularities at z = 0,1, t,∞ on the Riemann sphere C∪ {∞}. Exponents of
equation (2.1) atz= 0 (resp. z= 1,z=t,z=∞) are described by eigenvalues of the matrixA_{0}
(resp.A_{1},A_{t},−(A_{0}+A_{1}+A_{t})). By the transformationY →z^{n}^{0}(z−1)^{n}^{1}(z−t)^{n}^{t}Y, the system
of differential equations (2.1) is replaced as A(z) → A(z) + (n0/z+n1/(z−1) +n2/(z−t))I
(I: unit matrix), and we can transform equation (2.1) to the one where one of the eigenvalues
of A_{i} is zero for i∈ {0,1, t} by putting −n_{i} to be one of the eigenvalues of the original A_{i}. If
the exponents atz=∞ are distinct, then we can normalize the matrix−(A_{0}+A1+At) to be
diagonal by a suitable gauge transformation Y → GY, A(z) → GA(z)G^{−1}. In this paper we
assume that one of the eigenvalues of A_{i} is zero for i= 0,1, t and the matrix −(A_{0}+A_{1}+A_{t})
is diagonal, and we set

A∞=−(A_{0}+A_{1}+A_{t}) =

κ1 0
0 κ_{2}

. (2.2)

By eliminatingy_{2} in equation (2.1), we have a second-order linear differential equation,
d^{2}y_{1}

dz^{2} +p_{1}(z)dy_{1}

dz +p_{2}(z)y_{1}= 0, p_{1}(z) =−a_{11}(z)−a_{22}(z)−

d
dza_{12}(z)

a_{12}(z) ,
p_{2}(z) =a_{11}(z)a_{22}(z)−a_{12}(z)a_{21}(z)− d

dza_{11}(z) +a_{11}(z)_{dz}^{d}a_{12}(z)

a_{12}(z) . (2.3)

Set

Ai = a^{(i)}_{11} a^{(i)}_{12}
a^{(i)}_{21} a^{(i)}_{22}

!

, (i= 0,1, t). (2.4)

It follows from equation (2.2) that a^{(0)}_{12} +a^{(1)}_{12} +a^{(t)}_{12} = 0, a^{(0)}_{21} +a^{(1)}_{21} +a^{(t)}_{21} = 0. Hence a12(z)
and a_{21}(z) are expressed as

a_{12}(z) = k_{1}z+k_{2}

z(z−1)(z−t), a_{21}(z) = ˜k_{1}z+ ˜k_{2}
z(z−1)(z−t),
and we have

a^{(0)}_{12} +a^{(1)}_{12} +a^{(t)}_{12} = 0, (t+ 1)a^{(0)}_{12} +ta^{(1)}_{12} +a^{(t)}_{12} =−k_{1}, ta^{(0)}_{12} =k_{2},
a^{(0)}_{21} +a^{(1)}_{21} +a^{(t)}_{21} = 0, (t+ 1)a^{(0)}_{21} +ta^{(1)}_{21} +a^{(t)}_{21} =−˜k_{1}, ta^{(0)}_{21} = ˜k_{2}.

If k1 = k2 = 0, then y1 satisfies a first-order linear differential equation, and it is integrated
easily. Hence we assume that (k1, k2) 6= (0,0). Then it is shown that two of a^{(0)}_{12}, a^{(1)}_{12}, a^{(t)}_{12},
(t+ 1)a^{(0)}_{12} +ta^{(1)}_{12} +a^{(t)}_{12} cannot be zero. We setλ=−k_{2}/k1 (k1 6= 0) andλ=∞ (k1 = 0). The
condition that none of a^{(0)}_{12}, a^{(1)}_{12}, a^{(t)}_{12} nor (t+ 1)a^{(0)}_{12} +ta^{(1)}_{12} +a^{(t)}_{12} is zero is equivalent to that
λ6= 0,1, t,∞, and the condition a^{(0)}_{12} = 0 (resp.a^{(1)}_{12} = 0, a^{(t)}_{12} = 0, (t+ 1)a^{(0)}_{12} +ta^{(1)}_{12} +a^{(t)}_{12} = 0)
is equivalent toλ= 0 (resp.λ= 1, λ=t,λ=∞).

We consider the case λ6= 0,1, t,∞, i.e., the case a^{(0)}_{12} 6= 0, a^{(1)}_{12} 6= 0, a^{(t)}_{12} 6= 0, (t+ 1)a^{(0)}_{12} +
ta^{(1)}_{12} +a^{(t)}_{12} 6= 0. Letθ0 (resp.θ1,θt) and 0 be the eigenvalues of A0 (resp.A1,At). Then we can
set A0,A1,At as

A_{0} =

u_{0}+θ_{0} −w_{0}
u_{0}(u_{0}+θ_{0})/w_{0} −u_{0}

, A_{1} =

u_{1}+θ_{1} −w_{1}
u_{1}(u_{1}+θ_{1})/w_{1} −u_{1}

, At=

ut+θt −w_{t}
u_{t}(u_{t}+θ_{t})/w_{t} −u_{t}

, (2.5)

by introducing variables u0,w0,u1,w1, ut, wt. By taking trace of equation (2.2), we have the
relationθ_{0}+θ_{1}+θ_{t}+κ_{1}+κ_{2} = 0. We setθ∞=κ_{1}−κ_{2}, then we haveκ_{1} = (θ∞−θ_{0}−θ_{1}−θ_{t})/2,
κ_{2}=−(θ∞+θ_{0}+θ_{1}+θ_{t})/2.

We determineu0,u1,ut,w0,w1,wtso as to satisfy equation (2.2) and the following relations:

a_{12}(z) =−w_{0}

z − w_{1}

z−1 − w_{t}

z−t = k(z−λ) z(z−1)(z−t), a11(λ) = u0+θ0

λ +u1+θ1

λ−1 +ut+θt

λ−t =µ,

(see [11]). Namely, we solve the following equations for u0,u1,ut,w0,w1,wt:

−w_{0}−w_{1}−w_{t}= 0, w_{0}(t+ 1) +w_{1}t+w_{t}=k, −w_{0}t=−kλ,
u_{0}(u_{0}+θ_{0})/w_{0}+u_{1}(u_{1}+θ_{1})/w_{1}+u_{t}(u_{t}+θ_{t})/w_{t}= 0,

u0+θ0+u1+θ1+ut+θt=−κ_{1}, −u_{0}−u1−ut=−κ_{2},

(u0+θ0)/λ+ (u1+θ1)/(λ−1) + (ut+θt)/(λ−t) =µ. (2.6)
The linear equations for w_{0},w_{1},w_{t} are solved as

w0 = kλ

t , w1=−k(λ−1)

t−1 , wt= k(λ−t)

t(t−1). (2.7)

By the equations which are linear inu_{0},u_{1} and u_{t}, we can expressu_{1}+θ_{1} and u_{t}+θ_{t} as linear
functions in u0. We substitute u1+θ1 and ut+θt into a quadratic equation inu0, u1 and ut.
Then the coefficient of u^{2}_{0} disappears, andu0,u1,ut are solved as

u0=−θ_{0}+ λ
tθ∞

[λ(λ−1)(λ−t)µ^{2}+{2κ_{1}(λ−1)(λ−t)−θ1(λ−t)

−tθ_{t}(λ−1)}µ+κ_{1}{κ_{1}(λ−t−1)−θ_{1}−tθ_{t}}],
u1=−θ_{1}− λ−1

(t−1)θ∞

[λ(λ−1)(λ−t)µ^{2}+{2κ_{1}(λ−1)(λ−t) + (θ∞−θ1)(λ−t)

−tθ_{t}(λ−1)}µ+κ_{1}{κ_{1}(λ−t+ 1) +θ_{0}−(t−1)θ_{t}}],
ut=−θ_{t}+ λ−t

t(t−1)θ∞

[λ(λ−1)(λ−t)µ^{2}+{2κ_{1}(λ−1)(λ−t)−θ1(λ−t)

+t(θ∞−θ_{t})(λ−1)}µ+κ_{1}{κ_{1}(λ−t+ 1) +θ_{0}+ (t−1)(θ∞−θ_{t})}]. (2.8)
We denote the Fuchsian system of differential equations

dY dz =

A_{0}

z + A_{1}

z−1 + A_{t}
z−t

Y, Y =

y_{1}
y2

, (2.9)

with equations (2.5), (2.7), (2.8) byD_{Y}(θ0, θ1, θt, θ∞;λ, µ;k). Then the second-order differential
equation (2.3) is written as

d^{2}y1

dz^{2} +

1−θ0

z +1−θ1

z−1 +1−θt

z−t − 1 z−λ

dy1

dz +

κ_{1}(κ_{2}+ 1)

z(z−1) + λ(λ−1)µ

z(z−1)(z−λ)− t(t−1)H z(z−1)(z−t)

y_{1}= 0,

H = 1

t(t−1)[λ(λ−1)(λ−t)µ^{2}− {θ_{0}(λ−1)(λ−t) +θ_{1}λ(λ−t)

+ (θt−1)λ(λ−1)}µ+κ1(κ2+ 1)(λ−t)], (2.10)

which we denote by Dy1(θ0, θ1, θt, θ∞;λ, µ). This equation has regular singularities at z = 0,1, t, λ,∞. Exponents of the singularity z =λ are 0, 2, and it is apparent (non-logarithmic) singularity. Note that the differential equations

dλ dt = ∂H

∂µ, dµ

dt =−∂H

∂λ (2.11)

describe the condition for monodromy preserving deformation of equation (2.3) with respect to the variable t. By eliminating the variable µ in equation (2.11), we have the sixth Painlev´e equation on the variableλ(see equation (1.2)). See [20] on equations (2.3), (2.10) and (2.11).

We consider realization of the Fuchsian system (equation (2.1)) for the case λ= 0,1, t,∞ in the appendix.

### 3 The space of initial conditions for the sixth Painlev´ e equation and Heun’s equation

In this section, we introduce the space of initial conditions for the sixth Painlev´e equation, restrict the variables of the space of initial conditions E(t) to certain lines, and we obtain Heun’s equation.

The space of initial conditions was introduced by Okamoto [18], which is a suitable defining variety for the set of solutions to the Painlev´e system. In [22], Shioda and Takano studied the space of initial conditions further for the sixth Painlev´e system (equation (2.11)) to study roles of holomorphy on the Hamiltonian. It was also constructed as a moduli space of parabolic connections by Inaba, Iwasaki and Saito [8,9]. Here we adopt the coordinate of initial coordinate by Shioda and Takano [22] (see also [33]). The space of initial condition E(t) is defined by patching six copies

U_{0} ={(q_{0}, p_{0})}, U_{1}={(q_{1}, p_{1})}, U_{2}={(q_{2}, p_{2})},

U_{3} ={(q_{3}, p_{3})}, U_{4}={(q_{4}, p_{4})}, U∞={(q_{∞}, p∞)}, (3.1)
of C^{2} for fixed (t;θ_{0}, θ_{1}, θ_{t}, θ∞), and the rule of patching is defined by

q_{0}q∞= 1, q_{0}p_{0}+q∞p∞=−κ_{1}, (U_{0}∩U∞),
q_{0}p_{0}+q_{1}p_{1}=θ_{0}, p_{0}p_{1} = 1, (U_{0}∩U_{1}),
(q0−1)p0+q2p2 =θ1, p0p2 = 1, (U0∩U2),
(q0−t)p0+q3p3 =θt, p0p3 = 1, (U0∩U3),

q∞p∞+q4p4 = 1−θ∞, p∞p4= 1, (U∞∩U4). (3.2) The variables (λ, µ) of the sixth Painlev´e system (see equation (2.11)) are realized as q0 =λ, p0 =µ inU0.

We define complex lines in the space of initial conditions as follows:

L_{0} ={(0, p_{0})} ⊂U_{0}, L_{1}={(1, p_{0})} ⊂U_{0},
L_{t}={(t, p_{0})} ⊂U_{0}, L∞={(0, p_{∞})} ⊂U∞,
L^{∗}_{0} ={(q_{1},0)} ⊂U1, L^{∗}_{1}={(q_{2},0)} ⊂U2,

L^{∗}_{t} ={(q_{3},0)} ⊂U3, L^{∗}_{∞}={(q_{4},0)} ⊂U4. (3.3)
Set

U_{0}^{q}^{0}^{6=0,1,t} =U0\(L0∪L1∪Lt).

Then the space of initial conditions E(t) is a direct sum of the sets U_{0}^{q}^{0}^{6=0,1,t}, L0, L1, Lt,L∞,
L^{∗}_{0}, L^{∗}_{1}, L^{∗}_{t}, L^{∗}_{∞}. If (λ, µ) ∈ U_{0}^{q}^{0}^{6=0,1,t}, then λ 6= 0,1, t,∞ and equation (2.10) has five regular
singularities{0,1, t, λ,∞}.

Although equation (2.6) was considered on the set U_{0}^{q}^{0}^{6=0,1,t}, we may consider realization of
a second-order differential equation as equation (2.10) on the space of initial conditions E(t).

On the lines L_{0}, L_{1}, L_{t}, equation (2.10) is realized by setting λ= 0,1, t, and the equation is
written in the form of Heun’s equation

d^{2}y1

dz^{2} +
−θ_{0}

z +1−θ1

z−1 +1−θt

z−t dy1

dz +κ1(κ2+ 1)z+tθ0µ

z(z−1)(z−t) y_{1} = 0, (3.4)
d^{2}y_{1}

dz^{2} +

1−θ_{0}

z + −θ_{1}

z−1 +1−θ_{t}
z−t

dy_{1}

dz +κ_{1}(κ_{2}+ 1)(z−1) + (1−t)θ_{1}µ

z(z−1)(z−t) y_{1} = 0, (3.5)
d^{2}y_{1}

dz^{2} +

1−θ_{0}

z +1−θ_{1}

z−1 + −θ_{t}
z−t

dy_{1}

dz +κ_{1}(κ_{2}+ 1)(z−t) +t(t−1)θ_{t}µ

z(z−1)(z−t) y_{1}= 0, (3.6)
respectively. Note that if θ0θ1θt 6= 0 then we can realize all values of accessory parameter as
varyingµ. For the caseθ_{0}θ_{1}θ_{t}= 0, we should consider other realizations.

To realize equation (2.10) on the lineL^{∗}_{0}, we change the variables (λ, µ) into the ones (q1, p1)
on equation (2.10) by applying relations λµ+q_{1}p_{1} =θ_{0}, µp_{1}= 1. Then we have

d^{2}y_{1}
dz^{2} +

1−θ_{0}

z +1−θ_{1}

z−1 +1−θ_{t}

z−t − 1

z+p1(p1q1−θ0)
dy_{1}

dz

+κ1(κ2+ 1)z^{2}+ (tq1−θ0(θt+tθ1+p1pol_{1})z+ (p1q1−θ0)(−t−p1pol_{2})

z(z−1)(z−t)(z+p1(p1q1−θ0)) y1 = 0,
where pol_{1} and pol_{2} are polynomials inp1,q1,t,θ0,θ1,θt,θ∞. By settingp1 = 0, we obtain

d^{2}y1

dz^{2} +
−θ_{0}

z +1−θ1

z−1 +1−θt

z−t dy1

dz

+κ_{1}(κ_{2}+ 1)z^{2}+ (tq_{1}−θ_{0}(θ_{t}+tθ_{1}))z+tθ_{0}

z^{2}(z−1)(z−t) y_{1}= 0. (3.7)

Since the exponents of equation (3.7) atz = 0 are 1 andθ_{0}, we consider gauge-transformation
v1 =z^{−1}y1 to obtain Heun’s equation, and we have

d^{2}v1

dz^{2} +

2−θ0

z +1−θ1

z−1 +1−θt

z−t dv1

dz +(κ1+ 1)(κ2+ 2)z−q

z(z−1)(z−t) v_{1}= 0,

q =−tq_{1}+ (θ0−1){t(θ_{1}−1) +θt−1}. (3.8)

To realize the second-order Fuchsian equation on the line L^{∗}_{1}, we change the variables (λ, µ)
into the ones (q_{2}, p_{2}), substitutep_{2} = 0 into equation (2.10) and set v_{1}= (z−1)^{−1}y_{1}. Then v_{1}
satisfies the following equation;

d^{2}v_{1}
dz^{2} +

1−θ_{0}

z +2−θ_{1}

z−1 +1−θ_{t}
z−t

dv_{1}

dz +(κ_{1}+ 1)(κ_{2}+ 2)(z−1)−q

z(z−1)(z−t) v_{1}= 0,

q = (t−1)q2−(θ1−1){(1−t)(θ0−1) +θt−1}. (3.9)
The second-order Fuchsian equation on the line L^{∗}_{t} is realized as

d^{2}v_{1}
dz^{2} +

1−θ_{0}

z +1−θ_{1}

z−1 +2−θ_{t}
z−t

dv_{1}

dz +(κ_{1}+ 1)(κ_{2}+ 2)(z−t)−q

z(z−1)(z−t) v1 = 0,

q =t(1−t)q3−(θt−1)((t−1)(θ0−1) +t(θ1−1)), (3.10)
by setting p_{3} = 0 andv_{1} = (z−t)^{−1}y_{1}.

We investigate equation (2.10) on the line L∞. We change the variables (λ, µ) into the ones
(q∞, p∞) on equation (2.10) by applying relations λq∞ = 1, λµ+q∞p∞=−κ_{1}, and substitute
q∞= 0. Then we have

d^{2}y1

dz^{2} +

1−θ0

z +1−θ1

z−1 +1−θt

z−t dy1

dz +κ1(κ2+ 2)z−q

z(z−1)(z−t)y1 = 0,
q = (θ∞−1)p∞+κ_{1}(t(κ_{2}+θ_{t}+ 1) +κ_{2}+θ_{1}+ 1).

Note that the exponents atz=∞ are κ1 andκ2+ 2.

To realize equation (2.10) on the lineL^{∗}_{∞}, we change the variables (λ, µ) into the ones (q_{4}, p_{4})
on equation (2.10) by applying relations λq∞= 1, λµ+q∞p∞ =−κ_{1},q∞p∞+q4p4 = 1−θ∞,
p∞p4 = 1, substitutep4 = 0. We obtain

d^{2}y_{1}
dz^{2} +

1−θ_{0}

z +1−θ_{1}

z−1 +1−θ_{t}
z−t

dy_{1}

dz +(κ_{1}+ 1)(κ_{2}+ 1)z−q

z(z−1)(z−t) y_{1} = 0,

q =−q_{4}+ (κ_{2}+ 1)(t(κ_{1}+θ_{t}) +κ_{1}+θ_{1}). (3.11)
The exponents atz=∞areκ_{1}+ 1 andκ_{2}+ 1, which are different from the case of the lineL∞.
The Fuchsian systemD_{Y}(θ0, θ1, θt, θ∞;λ, µ;k) is originally defined on the set U_{0}^{q}^{0}^{6=0,1,t}. We
try to consider realization of Fuchsian system (equation (2.1)) on the lines L_{0},L^{∗}_{0}, L_{1}, L^{∗}_{1}, L_{t},
L^{∗}_{t},L∞,L^{∗}_{∞} in the appendix.

### 4 Middle convolution

First, we review an algebraic analogue of Katz’ middle convolution functor developed by Det-
tweiler and Reiter [2, 3], which we restrict to the present setting. Let A0, A1, At be matrices
inC^{2×2}. For ν∈C, we define the convolution matricesB_{0}, B_{1}, B_{t}∈C^{6×6} as follows:

B_{0}=

A0+ν A1 At

0 0 0

0 0 0

, B_{1}=

0 0 0

A_{0} A_{1}+ν A_{t}

0 0 0

,

B_{t}=

0 0 0

0 0 0

A0 A1 At+ν

. (4.1)

Letz∈C\ {0,1, t},γ_{p} (p∈C) be a cycle inC\ {0,1, t, z}turning the pointw=panti-clockwise
whose fixed base point is o ∈ C\ {0,1, t, z}, and [γ_{p}, γ_{p}^{0}] = γpγ_{p}^{0}γ_{p}^{−1}γ_{p}^{−1}0 be the Pochhammer
contour.

Proposition 1 ([3]). Assume thatY =^{t}(y1(z), y2(z))is a solution to the system of differential
equations

dY dz =

A_{0}

z + A_{1}

z−1 + A_{t}
z−t

Y.

For p∈ {0,1, t,∞}, the function

U =

Z

[γz,γp]

w^{−1}y1(w)(z−w)^{ν}dw
Z

[γz,γp]

w^{−1}y_{2}(w)(z−w)^{ν}dw
Z

[γz,γp]

(w−1)^{−1}y1(w)(z−w)^{ν}dw
Z

[γz,γp]

(w−1)^{−1}y2(w)(z−w)^{ν}dw
Z

[γz,γp]

(w−t)^{−1}y_{1}(w)(z−w)^{ν}dw
Z

[γz,γp]

(w−t)^{−1}y2(w)(z−w)^{ν}dw

,

satisfies the system of differential equations dU

dz =
B_{0}

z + B_{1}

z−1 + B_{t}
z−t

U. (4.2)

We set

L_{0} =

Ker(A0) 0 0

, L_{1} =

0
Ker(A_{1})

0

, L_{t}=

0
0
Ker(A_{t})

,

L=L_{0}⊕ L_{1}⊕ L_{t}, K= Ker(B0)∩Ker(B1)∩Ker(Bt), (4.3)
where L_{0}, L_{1}, L_{t}, K ⊂ C^{6} and 0 in equation (4.3) means the zero vector in C^{2}. We fix
an isomorphism between C^{6}/(K +L) and C^{m} for some m. A tuple of matrices mc_{ν}(A) =
( ˜B0,B˜1,B˜t), where ˜Bp (p = 0,1, t) is induced by the action of Bp on C^{m} ' C^{6}/(K +L),
is called an additive version of the middle convolution of (A_{0}, A_{1}, A_{t}) with the parameter ν.

LetA_{0},A_{1},A_{t} be the matrices defined by equation (2.5). Then it is shown that ifν = 0, κ_{1}, κ_{2}
(resp. ν 6= 0, κ_{1}, κ2) then dimC^{6}/(K+L) = 2 (resp. dimC^{6}/(K+L) = 3). If ν = 0, then the
middle convolution is identity (see [3]). Hence the middle convolutions for two cases ν =κ_{1}, κ_{2}
may lead to non-trivial transformations on the 2×2 Fuchsian system with four singularities
{0,1, t,∞}. Filipuk [5] obtained that the middle convolution for the case ν = κ1 induce an
Okamoto’s transformation of the sixth Painlev´e system.

We now calculate explicitly the Fuchsian system of differential equations determined by the
middle convolution for the case ν =κ2. Note that the following calculation is analogous to the
one in [30] for the case ν =κ_{1}. Ifν=κ_{2}, then the spaces L_{0},L_{1},L_{t},K are written as

L_{0} =C

w_{0}
u_{0}+θ_{0}

0 0 0 0

, L_{1} =C

0 0 w1

u_{1}+θ_{1}
0
0

, L_{t}=C

0
0
0
0
w_{t}
ut+θt

, K=C

0 1 0 1 0 1

.

Set

S =

0 0 0 w0 0 0

0 0 1 u0+θ0 0 0

0 0 0 0 w_{1} 0

s41 s42 1 0 u1+θ1 0

0 0 0 0 0 wt

s_{61} s_{62} 1 0 0 u_{t}+θ_{t}

,

s41= µ(λ−t) +κ_{1}
kκ1

, s61= t(µ(λ−1) +κ_{1})
kκ1

, s42=

˜λ−λ λ(λ−1)κ2

,
s_{62}= t(˜λ−λ)

λ(λ−t)κ_{2}, λ˜=λ− κ_{2}

µ−^{θ}_{λ}^{0} −_{(λ−1)}^{θ}^{1} −_{(λ−t)}^{θ}^{t} , (4.4)

and ˜U =S^{−1}U, where U is a solution to equation (4.2). Then detU =k^{2}(˜λ−λ)/(t(1−t)κ2)
and ˜U satisfies

dU˜ dz =

b_{11}(z) b_{12}(z) 0 0 0 0
b_{21}(z) b_{22}(z) 0 0 0 0

−(u0+θ0)θ∞t kκ1λz

λ˜

λz 0 0 0 0

t

kλz 0 0 ^{κ}_{z}^{2} 0 0

1−t

k(λ−1)(z−1) 0 0 0 _{z−1}^{κ}^{2} 0

t(1−t)

k(λ−t)(z−t) 0 0 0 0 _{z−t}^{κ}^{2}

U ,˜

where b_{11}(z), . . . , b_{22}(z) are calculated such that the system of differential equation
dY˜

dz =

b11(z) b12(z)
b_{21}(z) b_{22}(z)

Y ,˜ Y˜ =

u˜1(z)

˜
u_{2}(z)

,

coincides with the Fuchsian system D_{Y}(˜θ_{0},θ˜_{1},θ˜_{t},θ˜∞; ˜λ,µ; ˜˜ k) (see equation (2.9)), where
θ˜_{0}= θ_{0}−θ_{1}−θ_{t}−θ∞

2 , θ˜_{1}= −θ_{0}+θ_{1}−θ_{t}−θ∞

2 , θ˜_{t}= −θ_{0}−θ_{1}+θ_{t}−θ∞

2 ,

θ˜∞= −θ_{0}−θ1−θt+θ∞

2 , λ˜=λ− κ2

µ−^{θ}_{λ}^{0} −_{λ−1}^{θ}^{1} −_{λ−t}^{θ}^{t} ,

˜

µ= κ_{2}+θ_{0}

˜λ + κ_{2}+θ_{1}

λ˜−1 +κ_{2}+θ_{t}
λ˜−t + κ_{2}

λ−λ˜, k˜=k. (4.5)

The functions ˜u1(z) and ˜u2(z) are expressed as

˜

u1(z) = (u0+θ0)u1(z)−kλ

t u2(z) + (u1+θ1)u3(z) +k(λ−1)

t−1 u_{4}(z) + (u_{t}+θ_{t})u_{5}(z) +k(λ−t)
t(1−t)u_{6}(z),

˜

u_{2}(z) = κ_{2}λ(λ−1)(λ−t)
κ1(λ−λ)˜

(λµ+κ_{1})(u_{0}+θ_{0})

kλ u_{1}(z)−λµ+κ_{1}
t u_{2}(z)
+((λ−1)µ+κ_{1})(u_{1}+θ_{1})

k(λ−1) u_{3}(z) +(λ−1)µ+κ_{1}
t−1 u_{4}(z)
+ ((λ−t)µ+κ_{1})(u_{t}+θ_{t})

k(λ−t) u_{5}(z) +(λ−t)µ+κ_{1}
t(1−t) u_{6}(z)

. (4.6)

Combining Proposition1 with equation (4.6) and setting ˜y1(z) = ˜u1(z), ˜y2(z) = ˜u2(z), we have the following theorem by means of a straightforward calculation:

Theorem 1. Set κ1 = (θ∞−θ0 −θ1 −θt)/2 and κ2 = −(θ_{∞}+θ0 +θ1+θt)/2. If y1(z) is
a solution to the Fuchsian equationD_{y}_{1}(θ_{0}, θ_{1}, θ_{t}, θ∞;λ, µ), then the functionY˜ =^{t}(˜y_{1}(z),y˜_{2}(z))
defined by

˜ y1(z) =

Z

[γz,γp]

dy1(w)

dw (z−w)^{κ}^{2}dw, (4.7)

˜

y_{2}(z) = κ_{2}λ(λ−1)(λ−t)
k(λ−λ)˜

Z

[γz,γp]

dy_{1}(w)

dw −µy_{1}(w)
1

λ−w+ µ κ1

dy_{1}(w)
dw

(z−w)^{κ}^{2}dw,
satisfies the Fuchsian system D_{Y}(κ_{2}+θ_{0}, κ_{2}+θ_{1}, κ_{2}+θ_{t}, κ_{2}+θ∞; ˜λ,µ;˜ k) for p∈ {0,1, t,∞},
where

λ˜=λ− κ2

µ− ^{θ}_{λ}^{0} −_{λ−1}^{θ}^{1} −_{λ−t}^{θ}^{t} , µ˜= κ2+θ0

λ˜ +κ2+θ1

λ˜−1 +κ2+θt

λ˜−t + κ2

λ−˜λ. (4.8) Since

0 = Z

[γz,γp]

d

dw(y1(w)(z−w)^{κ}^{2})dw

= Z

[γz,γp]

dy_{1}(w)

dw (z−w)^{κ}^{2}dw+κ_{2}
Z

[γz,γp]

y_{1}(w)(z−w)^{κ}^{2}^{−1}dw, (4.9)
we have

Proposition 2 ([17]). If y1(z) is a solution to Dy1(θ0, θ1, θt, θ∞;λ, µ), then the function

˜ y(z) =

Z

[γz,γp]

y1(w)(z−w)^{κ}^{2}^{−1}dw, (4.10)

satisfiesDy1(κ2+θ0, κ2+θ1, κ2+θt, κ2+θ∞; ˜λ,µ)˜ forp∈ {0,1, t,∞}, where˜λandµ˜are defined in equation (4.8).

Note that this proposition was obtained by Novikov [17] by another method. Kazakov
and Slavyanov [14] essentially obtained this proposition by investigating Euler transformation
of 2×2 Fuchsian systems with singularities {0,1, t,∞} which are realized differently from
D_{Y}(θ_{0}, θ_{1}, θ_{t}, θ∞;λ, µ, k).

Let us recall the symmetry of the sixth Painlev´e equation. It was essentially established by
Okamoto [19] that the sixth Painlev´e equation has symmetry of the affine Weyl groupW(D_{4}^{(1)}).

More precisely, the sixth Painlev´e system is invariant under the following transformations, which
are involutive and satisfy Coxeter relations attached to the Dynkin diagram of type D^{(1)}_{4} , i.e.

(si)^{2}= 1 (i= 0,1,2,3,4),sjs_{k} =s_{k}sj (j, k∈ {0,1,3,4}), sjs2sj =s2sjs2 (j = 0,1,3,4):

θ_{t} θ∞ θ_{1} θ_{0} λ µ t

s_{0} −θ_{t} θ∞ θ_{1} θ_{0} λ µ− _{λ−t}^{θ}^{t} t

s_{1} θ_{t} 2−θ∞ θ_{1} θ_{0} λ µ t

s_{2} κ_{1}+θ_{t} −κ_{2} κ_{1}+θ_{1} κ_{1}+θ_{0} λ+^{κ}_{µ}^{1} µ t

s_{3} θ_{t} θ∞ −θ_{1} θ_{0} λ µ− _{λ−1}^{θ}^{1} t

s_{4} θ_{t} θ∞ θ_{1} −θ_{0} λ µ−^{θ}_{λ}^{0} t

i

i

i

i i

0

3

1

4 2

The map (θ_{0}, θ_{1}, θ_{t}, θ∞;λ, µ) 7→ (˜θ_{0},θ˜_{1},θ˜_{t},θ˜∞; ˜λ,µ) determined by equation (4.5) coincides˜
with the composition map s_{0}s_{3}s_{4}s_{2}s_{0}s_{3}s_{4}, because

(θ0, θ1, θt, θ∞;λ, µ)^{s}^{0}7→^{s}^{3}^{s}^{4} −θ0,−θ_{1},−θ_{t}, θ∞;λ, µ−^{θ}_{λ}^{0} −_{λ−1}^{θ}^{1} −_{λ−t}^{θ}^{t}

s2

7→ −κ2−θ0,−κ_{2}−θ1,−κ_{2}−θt, κ1; ˜λ, µ−^{θ}_{λ}^{0} −_{λ−1}^{θ}^{1} −_{λ−t}^{θ}^{t}

s0s3s4

7→ κ2+θ0, κ2+θ1, κ2+θt, κ2+θ∞; ˜λ,µ˜ .

Therefore, if we know a solution to the Fuchsian system D_{Y}(θ_{0}, θ_{1}, θ_{t}, θ∞;λ, µ;k), then we have
integral representations of solutions to the Fuchsian system D_{Y}(˜θ_{0},θ˜_{1},θ˜_{t},θ˜∞; ˜λ,µ;˜ k) obtained
by the transformation s0s3s4s2s4s3s0. Note that the transformations si (i = 0,1,2,3,4) are
extended to isomorphisms of the space of initial conditions E(t).

We recall the middle convolution for the caseν=κ_{1}.

Proposition 3 ([30, Proposition 3.2]). If Y = ^{t}(y_{1}(z), y_{2}(z)) is a solution to the Fuch-
sian system DY(θ0, θ1, θt, θ∞;λ, µ;k) (see equation (2.9)), then the function Y˜ =^{t}(˜y1(z),y˜2(z))
defined by

˜
y_{1}(z) =

Z

[γz,γp]

κ_{1}y_{1}(w) + (w−˜λ)dy_{1}(w)
dw

(z−w)^{κ}^{1}
w−λ dw,

˜

y2(z) = −θ_{∞}
κ2

Z

[γz,γp]

dy2(w)

dw (z−w)^{κ}^{1}dw, (4.11)

satisfies the Fuchsian system D_{Y}(κ_{1}+θ_{0}, κ_{1}+θ_{1}, κ_{1}+θ_{t},−κ_{2};λ+κ_{1}/µ, µ;k)for p∈ {0,1, t,∞}.

The parameters (κ1+θ0, κ1+θ1, κ1+θt,−κ_{2};λ+κ1/µ, µ) are obtained from the parameters
(θ0, θ1, θt, θ∞;λ, µ) by applying the transformation s2. Note that the relationship the transfor-
mations_{2}was obtained by Filipuk [5] explicitly (see also [7]), and Boalch [1] and Dettweiler and
Reiter [4] also obtained results on the symmetry of the sixth Painlev´e equation and the middle
convolution.

### 5 Middle convolution, integral transformations

### of Heun’s equation and the space of initial conditions

In this section, we investigating relationship among the middle convolution, integral transfor- mations of Heun’s equation and the space of initial conditions.

Kazakov and Slavyanov established an integral transformation on solutions to Heun’s equa- tion in [13], which we express in a slightly different form.

Theorem 2 ([13]). Set

(η−α)(η−β) = 0, γ^{0} =γ+ 1−η, δ^{0}=δ+ 1−η, ^{0} =+ 1−η,
{α^{0}, β^{0}}={2−η,−2η+α+β+ 1},

q^{0} =q+ (1−η)(+δt+ (γ−η)(t+ 1)). (5.1)

Let v(w) be a solution to
d^{2}v

dw^{2} +
γ^{0}

w + δ^{0}

w−1+ ^{0}
w−t

dv

dw + α^{0}β^{0}w−q^{0}

w(w−1)(w−t)v= 0. (5.2)

Then the function y(z) =

Z

[γz,γp]

v(w)(z−w)^{−η}dw
is a solution to

d^{2}y
dz^{2} +

γ z + δ

z−1 + z−t

dy

dz + αβz−q

z(z−1)(z−t)y= 0, (5.3)

for p∈ {0,1, t,∞}.

Here we derive Theorem 2 by considering the limit λ → 0 in Proposition 2. Let us recall
notations in Proposition 2. We consider the limitλ→0 while fixingµ for the caseθ_{0} 6= 0 and
θ_{0}+κ_{2} 6= 0. Then we have ˜λ→0 and ˜µ→(tθ_{0}µ+κ_{2}(t(κ_{1}+θ_{t}) +κ_{1}+θ_{1}))/(t(κ_{2}+θ_{0})). Hence
it follows from Proposition 2 and equation (3.4) that, ify(z) satisfies

d^{2}y(z)
dz^{2} +

−θ_{0}

z +1−θ1

z−1 + 1−θt

z−t

dy(z)

dz +κ1(κ2+ 1)z+tθ0µ

z(z−1)(z−t) y(z) = 0, (5.4) then the function

˜ y(z) =

Z

[γz,γp]

y(w)(z−w)^{κ}^{2}^{−1}dw, (5.5)

satisfies
d^{2}y(z)˜

dz^{2} +

−κ_{2}−θ_{0}

z +1−κ_{2}−θ_{1}

z−1 + 1−κ_{2}−θ_{t}
z−t

d˜y(z) dz +

θ∞(1−κ_{2})z+t(κ_{2}+θ_{0})^{tθ}^{0}^{µ+κ}^{2}^{(t(κ}_{t(κ}^{1}^{+θ}^{t}^{)+κ}^{1}^{+θ}^{1}^{))}

2+θ0)

z(z−1)(z−t)

y(z) = 0.˜ (5.6)
By setting γ = −κ_{2} −θ_{0}, δ = 1−κ_{2} −θ_{1}, = 1−κ_{2} −θ_{t}, α = η = 1−κ_{2}, β = θ∞,
q =−{tθ_{0}µ+κ2(t(κ1+θt)+κ1+θ1))}and comparing with the standard form of Heun’s equation
(equation (1.1)), we recover Theorem 2. Note that we can obtain the formula corresponding to
the case θ_{0}= 0 (resp. θ_{0}+κ_{2} = 0) by considering the limit θ_{0} →0 (resp.θ_{0}+κ_{2} →0).

The limitλ→0 while fixingµimplies the restriction of the coordinate (λ, µ) to the lineL0

in the space of initial conditionsE(t), and the line L0 with the parameter (θ0, θ1, θt, θ∞;λ, µ) is
mapped to the lineL_{0}in the space of initial conditions with the parameter (κ_{2}+θ_{0}, κ_{2}+θ_{1}, κ_{2}+θ_{t},
κ2+θ∞; ˜λ,µ) where ˜˜ λ and ˜µ are defined in equation (4.8), because ˜λ → 0 and ˜µ converges
by the limit. It follows from equations (5.4), (5.5), (5.6) that the integral transformation in
Proposition 2 reproduces the integral transformation on Heun’s equations in Theorem 2 by
restricting to the line L0. We can also establish that the line L1 (resp. Lt) in the space of
initial conditions with the parameter (θ0, θ1, θt, θ∞;λ, µ) is mapped to the line L1 (resp. Lt)
with the parameter (κ_{2}+θ_{0}, κ_{2} +θ_{1}, κ_{2}+θ_{t}, κ_{2} +θ∞; ˜λ,µ) by taking the limit˜ λ → 1 (resp.

λ→t), and the integral transformation in Proposition 2reproduces the integral transformation on Heun’s equations in Theorem2. We discuss the restriction of the map (θ0, θ1, θt, θ∞;λ, µ)7→

(κ_{2}+θ_{0}, κ_{2}+θ_{1}, κ_{2}+θ_{t}, κ_{2}+θ∞; ˜λ,µ) to the line˜ L^{∗}_{∞}. Let (q_{4}, p_{4}) (resp. (˜q_{4},p˜_{4})) be the coordinate
of U_{4} for the parameters (θ_{0}, θ_{1}, θ_{t}, θ∞;λ, µ) (resp. (κ_{2} +θ_{0}, κ_{2} +θ_{1}, κ_{2} +θ_{t}, κ_{2} +θ∞; ˜λ,µ)˜
(see equations (3.1), (3.2)). Then we can express ˜q4 and ˜p4 by the variables q4 and p4. By
setting p_{4} = 0, we have ˜p_{4} = 0 and ˜q_{4} = q_{4} −κ_{2}(t(κ_{1} +θ_{t}−1) +κ_{1} +θ_{1} −1). Hence the
line L^{∗}_{∞} with the parameter (θ_{0}, θ_{1}, θ_{t}, θ∞;λ, µ) is mapped to the line L^{∗}_{∞} with the parameter
(κ2 +θ0, κ2 +θ1, κ2 +θt, κ2 +θ∞; ˜λ,µ). It follows from Proposition˜ 2 that if y1(z) satisfies
equation (3.11) then the function ˜y(z) defined by Proposition 2 satisfies Heun’s equation with
the parameters γ = 1−θ_{0}−κ_{2}, δ = 1−θ_{1} −κ_{2}, = 1−θ_{t}−κ_{2}, α = 1−κ_{2}, β = 1 +θ∞,
q =−q_{4}−(1+t)κ2+(t(κ1+θt)+κ1+θ1)), and the integral representation reproduces Theorem2
by setting η=α= 1−κ_{2}. Therefore we have the following theorem:

Theorem 3. Let X = L0, L1, Lt or L^{∗}_{∞}. By the map s0s3s4s2s4s3s0 : (θ0, θ1, θt, θ∞;λ, µ) 7→

(κ_{2}+θ_{0}, κ_{2}+θ_{1}, κ_{2}+θ_{t}, κ_{2}+θ∞; ˜λ,µ)˜ where λ˜ and µ˜ are defined in equation (4.8), the line X
in the space of initial conditions with the parameter (θ0, θ1, θt, θ∞;λ, µ) is mapped to the line X
in the space of initial conditions with the parameter (κ2 +θ0, κ2 +θ1, κ2 +θt, κ2 +θ∞; ˜λ,µ)˜
where λ˜ and µ˜ are defined in equation (4.8), and the integral transformation in Proposition 2
determined by the middle convolution reproduces the integral transformation on Heun’s equations
in Theorem 2 by the restriction to the line X.